`(x-3)^2+y^2 =1 ` Find the volume of the torus generated by revolving the region bounded by the graph of the circle about the y-axis.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To find the volume of the torus generated by revolving the region bounded by the graph of circle about the y-axis, we may apply Washer method. In this method, rectangular strip representation that is perpendicular to the axis of rotation. We follow the formula  for Washer method: `V =pi int_a^b[(f(y))^2-(g(y))^2]dy` using a horizontal rectangular strip representation with thickness of `dy` .

The given equation: `(x-3)^2 +y^2=1` is in a form of` (x-R)^2+y^2=r^2` .

We set up the function of each radius based on the following formula:

inner radius: `f(y)= R -sqrt(r^2-y^2)`  

Then the function for the graph from x=3 to x=4 will be: `f(y)= 3-sqrt(1 -y^2)`

outer radius: `g(y)= R+sqrt(r^2-y)` 

Then the function for the graph from x=2 to x=3 will be: `g(y)= 3+sqrt(1-y^2)`

From the attached image, the boundary values of y are: `a= -1` and `b =1` .

Plug-in the values on the formula, we set up:

`V =pi int_(-1)^(1) [(3+sqrt(1-y^2))^2-(3-sqrt(1 -y^2))^2]dy`

`=pi int_(-1)^(1) [(3+6sqrt(1-y^2) +1-y^2)-(3-6sqrt(1 -y^2) +1 -y^2)]dy`

`=pi int_(-1)^(1) [ 3+6sqrt(1-y^2) +1-y^2 -3+6sqrt(1 -y^2) -1 +y^2]dy`

`=pi int_(-1)^(1) [12sqrt(1-y^2)]dy`

Apply the basic integration property: `int c f(x) dx - c int f(x) dx` .

`V =12pi int_(-1)^(1) [sqrt(1-y^2)]dy`

From integration table, we may apply the integral formula for function with roots: 

`int sqrt(a^2-u^2)du= (u*sqrt(a^2-u^2))/2+a^2/2 arcsin(u/a)`


`V =12pi int_(-1)^(1) [sqrt(1-y^2)]dy`

` = 12pi * [(y*sqrt(1-y^2))/2+1/2 arcsin(y/1)] |_(-1)^(1)`

`= 12pi * [(ysqrt(1-y^2))/2+ arcsin(y)/2] |_(-1)^(1)`

`=[6piysqrt(1-y^2)+ 6piarcsin(y)] |_(-1)^(1)`

Apply definite integral formula:  .

`V =[6piysqrt(1-y^2)+ 6piarcsin(y)] |_(-1)^(1)`

`=[6pi(1)sqrt(1-1^2)+ 6piarcsin(1)]-[6pi(-1)sqrt(1-(-1)^2)+ 6piarcsin(-1)]`

`=[6pisqrt(1-1)+ 6piarcsin(1)]-[-6pisqrt(1-1)+ 6piarcsin(-1)]`

`=[6pisqrt(0)+ 6piarcsin(1)]-[-6pisqrt(0)+ 6piarcsin(-1)]`

`=[6pi*0+ 6pi*(pi/2)]-[-6pi*0+ 6pi*(-pi/2))]`

`=[0+ 3pi^2]-[0+ (-3pi^2)]`

`= 3pi^2 -(-3pi^2)`

`=3pi^2 +3pi^2`

=`6pi^2`  or` 59.22` (approximated value)

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Image (1 of 1)
Approved by eNotes Editorial